High-toughness heat-conducting ceramic material and new energy battery cover plate

By developing a high-tough thermally conductive ceramic material containing alumina, zirconia, thermal toughener and beryllium oxide coated with one-dimensional carbon material, the weight, sealing, corrosion resistance and heat dissipation properties of traditional battery box and cover plates is solved, and excellent mechanical properties, thermal conductivity and toughness are achieved, which is suitable for new energy battery cover plates.

CN119707466APending Publication Date: 2025-03-28天津大学浙江研究院
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890511.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The traditional metal battery box and cover plate have a large weight, poor sealing, poor corrosion resistance, complex processing technology and low impact strength, which is not conducive to lightweight design of automobiles, and the thermal conductivity of alumina is low, which cannot meet the heat dissipation needs of battery cover plates.

Method used

Provide a high-tough thermal conductivity ceramic material, including alumina, zirconium oxide, thermal toughening agent and beryllium oxide coated one-dimensional carbon material, and ceramic materials with excellent mechanical properties, thermal conductivity and toughness are prepared through plasma surface roughening treatment and high-temperature sintering and other processes.

Benefits of technology

The material's bending strength reaches 250MPa, the thermal conductivity reaches 70W/(m·K), and the fracture toughness reaches 8MPa·m1/2. It can meet the needs of new energy battery covers and improve the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707466A_ABST
    Figure CN119707466A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness heat-conducting ceramic material and a new energy battery cover plate. The material comprises the following raw materials in parts by weight: 70-85 parts of aluminum oxide; 10 to 15 parts of zirconium oxide; 8-12 parts of a heat conduction toughening agent; 5-10 parts of a beryllium oxide coated one-dimensional carbon material; wherein the heat-conducting toughening agent comprises long-chain amino acid modified silica gel particles and graphitized carbon. According to the high-toughness heat-conducting ceramic material disclosed by the invention, on one hand, the one-dimensional carbon material is coated with beryllium oxide to form a network structure, so that super-strong mechanical properties are provided for the material; on the other hand, the heat-conducting toughening agent is added, and the heat-conducting toughening agent comprises graphitized carbon, long-chain amino acid modified silica gel particles and high polymers, so that the toughness, the strength and the heat-conducting property of the material are remarkably improved, and the requirements of the new energy battery cover plate can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of ceramic materials, and specifically relates to a high-toughness thermally conductive ceramic material and a new energy battery cover. Background Art

[0002] As the core component of new energy vehicles, the safety of power batteries directly affects the safety of the entire vehicle. The power battery system of pure electric vehicles is usually arranged under the floor of the vehicle body, and the operating environment is relatively harsh. The battery box and cover, as the carrier of the power battery, play a key role in the safe operation and protection of the battery pack. Its safety, reliability and durability are extremely important and determine the performance of the entire vehicle.

[0003] At present, traditional battery cases and covers are made of metal materials, such as steel or aluminum alloy. On the one hand, metal cases and covers are heavy, which will reduce the energy efficiency of the battery. On the other hand, they have poor sealing, which can easily cause the battery to be immersed in water and cause a short circuit. Thirdly, they have poor corrosion resistance. In addition, they also have defects such as complex processing technology and low impact strength, which is not conducive to achieving lightweight design of automobiles.

[0004] Alumina is a widely used material for small and medium power ceramic substrates. It has relatively high mechanical strength, abundant sources and low prices, but its thermal conductivity is low, about 20W / (m·K), which is far from meeting the heat dissipation requirements of battery cover plates. Summary of the invention

[0005] The purpose of this application is to provide a high-toughness thermally conductive ceramic material and a new energy battery cover to solve the technical problems in the prior art that traditional metal battery cases and covers are heavy, have poor sealing, poor corrosion resistance, complex processing technology, and low impact strength, which are not conducive to lightweight design of automobiles, while alumina has low thermal conductivity and cannot meet the heat dissipation requirements of the battery cover.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a high-toughness thermally conductive ceramic material, comprising the following raw materials in parts by weight:

[0007] 70-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 8-12 parts of thermal conductive toughening agent; 5-10 parts of beryllium oxide-coated one-dimensional carbon material;

[0008] Wherein, the thermal conductive toughening agent includes long-chain amino acid modified silica gel particles and graphitized carbon.

[0009] In one or more embodiments, the particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material is 0.5 to 5 μm, and the particle size of aluminum oxide and zirconium oxide is 0.5 to 5 μm.

[0010] In one or more embodiments, the thermal conductive toughening agent comprises the following components in parts by weight:

[0011] 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 6-10 parts of long-chain amino acid modified silica gel particles, and 15-20 parts of high polymer;

[0012] The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer.

[0013] In one or more embodiments, the beryllium oxide-coated one-dimensional carbon material is beryllium oxide-coated carbon fiber or beryllium oxide-coated carbon nanotube.

[0014] In one or more embodiments, the high-toughness thermally conductive ceramic material has a flexural strength of ≥250 MPa, a thermal conductivity of ≥70 W / (m·K), and a fracture toughness of ≥8 MPa·m 1 / 2 .

[0015] In order to achieve the above object, the second aspect of the present application provides a method for preparing the high-toughness thermally conductive ceramic material described in any one of the above embodiments, comprising:

[0016] Beryllium oxide is added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 4 to 6 hours to obtain a first intermediate product;

[0017] The first intermediate product is aged and centrifuged, and the precipitate is washed, dried, calcined, and ultrafinely ground to 0.5 to 5 μm to obtain a beryllium oxide-coated one-dimensional carbon material;

[0018] The aluminum oxide and the zirconium oxide are mixed and ball-milled, and then uniformly mixed with the beryllium oxide-coated one-dimensional carbon material and subjected to plasma surface roughening treatment to obtain a second intermediate product;

[0019] The second intermediate product and the thermal conductive toughening agent are mixed uniformly and pre-sintered, and ultra-finely ground to 3-10 μm to obtain a third intermediate product;

[0020] The third intermediate product is ball-milled again, dried, granulated, and pressed to obtain a rough blank;

[0021] The rough blank is sintered at high temperature to obtain a high-toughness thermally conductive ceramic material.

[0022] In one or more embodiments, the step of adding beryllium oxide to water, then adding a one-dimensional carbon material and Tween-80, and stirring for 4 to 6 hours to obtain the first intermediate product further comprises:

[0023] The one-dimensional carbon material is subjected to plasma surface roughening treatment.

[0024] In one or more embodiments, in the steps of aging and centrifuging the first intermediate product, washing, drying and calcining the precipitate, the calcination temperature is 950 to 1600° C. and the calcination time is 3 to 5 hours.

[0025] In one or more embodiments, in the step of uniformly mixing the second intermediate product and the thermally conductive toughening agent and pre-firing, the pre-firing is performed under an inert atmosphere, the pre-firing temperature is 900 to 1000° C., and the pre-firing time is 1 to 2 hours;

[0026] In the step of sintering the rough blank at high temperature, the temperature of the high temperature sintering is 1350-1500° C., and the time of the high temperature sintering is 1-4 hours.

[0027] In order to achieve the above-mentioned purpose, the third aspect of the present application provides a new energy battery cover plate, which is prepared using the high-toughness thermally conductive ceramic material described in any of the above-mentioned embodiments.

[0028] Different from the prior art, the beneficial effects of this application are:

[0029] The high-toughness thermally conductive ceramic material of the present application forms a network structure by coating a one-dimensional carbon material with beryllium oxide, which provides the material with super strong mechanical properties; on the other hand, a thermally conductive toughening agent is added, and the thermally conductive toughening agent includes graphitized carbon, long-chain amino acid modified silica gel particles and high polymers, which significantly improves the toughness, strength and thermal conductivity of the material, and can meet the needs of new energy battery cover plates;

[0030] The preparation method of the present application can introduce an etching effect on the surface of the material by performing plasma surface roughening treatment on the one-dimensional carbon material and the mixture of aluminum oxide, zirconium oxide and beryllium oxide coated one-dimensional carbon material, making the surface rougher, thereby increasing the contact area of ​​the material and improving the mechanical bonding force; in addition, after the surface roughening treatment, the interface performance between the materials can be improved, thereby enhancing the mechanical properties of the composite material; the improved interface performance also helps to improve the durability and stability of the composite material;

[0031] The material of the present application has excellent flexural strength, fracture toughness and thermal conductivity, among which the flexural strength reaches 250MPa, the thermal conductivity reaches 70W / (m·K), and the fracture toughness reaches 8MPa·m 1 / 2 , which can meet the needs of new energy battery covers. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a schematic flow chart of an implementation method of a method for preparing a high-toughness thermally conductive ceramic material of the present application. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0035] At present, due to the need for heat dissipation, new energy battery covers are generally made of metals with excellent heat dissipation performance. Metals have defects such as heavy weight, poor sealing, poor corrosion resistance, complex processing technology and low impact strength, which are not conducive to the lightweight design of automobiles and the improvement of energy efficiency.

[0036] In order to solve the above problems, the applicant has developed a high-toughness thermally conductive ceramic material, which has high mechanical strength and low cost on the one hand, and high thermal conductivity on the other hand, which can meet the needs of new energy battery cover plates.

[0037] Specifically, in one embodiment, the high-toughness thermally conductive ceramic material of the present application includes the following raw materials in parts by weight:

[0038] 70-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 8-12 parts of thermal conductive toughening agent; 5-10 parts of beryllium oxide-coated one-dimensional carbon material.

[0039] Among them, the thermal conductive toughening agent includes long-chain amino acid modified silica gel particles and graphitized carbon.

[0040] The high-toughness thermally conductive ceramic material based on the above components, on the one hand, can provide the material with super mechanical properties by coating the one-dimensional carbon material with beryllium oxide; on the other hand, the thermal conductivity and toughness of the material are significantly improved by the thermal conductive toughening agent, so that the material can have excellent strength, toughness and thermal conductivity.

[0041] In one embodiment, the beryllium oxide-coated one-dimensional carbon material may be specifically beryllium oxide-coated carbon fiber; in another embodiment, the beryllium oxide-coated one-dimensional carbon material may also be beryllium oxide-coated carbon nanotube.

[0042] One-dimensional carbon materials play the role of short fiber toughening. Due to the super strong mechanical properties of one-dimensional carbon materials, more energy is consumed when pulling out and breaking, which is beneficial to prevent the expansion of ceramic cracks. Beryllium oxide coating is used to improve the dispersion performance of one-dimensional carbon materials, so that they are evenly dispersed in the material to form a network.

[0043] In one embodiment, the thermally conductive toughening agent may include the following components in parts by weight:

[0044] 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 6-10 parts of long-chain amino acid modified silica gel particles, and 15-20 parts of high polymer.

[0045] The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer. The above-mentioned thermal conductive toughening agent can be prepared by mixing and stirring the components, and its preparation method is not described here.

[0046] The long-chain amino acid modified silica gel particles can be any long-chain amino acid grafted silica gel commonly used in the art, such as arginine grafted silica gel, etc., which can achieve the effect of this embodiment. The grafted amino acid can significantly improve the hydrophilicity of the material, thereby increasing the sintering density during sintering, which helps to improve the mechanical properties and thermal conductivity of the material.

[0047] In order to further optimize the thermal conductivity of the material, in one embodiment, the particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material can be 0.5-5 μm, and the particle size of aluminum oxide and zirconium oxide can be 0.5-5 μm. The overall thermal conductivity of the material can be significantly improved by using raw materials with ultrafine particle sizes.

[0048] Based on the high-toughness thermally conductive ceramic material of the above-mentioned embodiments, the thermal conductive toughening agent includes graphitized carbon, long-chain amino acid modified silica gel particles and high polymer. The graphitized carbon can improve the thermal conductivity of the material, and the long-chain amino acid modified silica gel particles can improve the hydrophilicity of the mixture, thereby increasing the sintering density, which is helpful to improve the thermal conductivity and mechanical properties of the material. The high polymer further improves the strength and toughness of the material, thereby significantly improving the toughness, strength and thermal conductivity of the material, which can meet the needs of new energy battery cover plates.

[0049] This application also provides a method for preparing the above-mentioned high-toughness thermally conductive ceramic material. Figure 1 , Figure 1It is a schematic flow chart of an implementation method of a method for preparing a high-toughness thermally conductive ceramic material of the present application.

[0050] like Figure 1 As shown, the preparation method comprises:

[0051] S100, adding beryllium oxide into water, and then adding one-dimensional carbon material and Tween-80, stirring for 4 to 6 hours to obtain a first intermediate product.

[0052] S200, aging and centrifuging the first intermediate product, washing, drying, calcining, and ultrafinely grinding the precipitate to 0.5-5 μm to obtain a beryllium oxide-coated one-dimensional carbon material.

[0053] First, the beryllium oxide-coated one-dimensional carbon material can be prepared by a method of stirring and mixing followed by calcination, and after the calcination, ultrafine grinding is performed to ensure the particle size of the material.

[0054] In one embodiment, the calcination temperature may be 950-1600° C., and the calcination time may be 3-5 hours.

[0055] In one embodiment, in order to optimize the coating effect of beryllium oxide on the one-dimensional carbon material and improve the mechanical properties of the subsequent material, before S100, the following steps are further included:

[0056] S10, performing plasma surface roughening treatment on the one-dimensional carbon material.

[0057] Through surface roughening treatment, etching can be introduced on the surface of carbon fiber to make the surface rougher, thereby increasing the contact area with beryllium oxide and improving mechanical bonding strength; in addition, surface roughening treatment can improve the interface performance between carbon materials and other materials, thereby enhancing the mechanical properties of composite materials; improved interface performance also helps to improve the durability and stability of composite materials.

[0058] Furthermore, after the beryllium oxide-coated one-dimensional carbon material is prepared, the method further comprises:

[0059] S300, mixing aluminum oxide and zirconium oxide and ball milling them, then uniformly mixing them with the beryllium oxide-coated one-dimensional carbon material and performing plasma surface roughening treatment to obtain a second intermediate product.

[0060] By performing plasma surface roughening treatment on one-dimensional carbon materials coated with alumina, zirconium oxide and beryllium oxide, an etching effect can be introduced on the material surface, thereby increasing the contact area and mechanical bonding force of each material, improving the interface performance, and enhancing the mechanical properties, durability and stability of the composite materials.

[0061] S400, the second intermediate product and the thermal conductive toughening agent are uniformly mixed and pre-burned, and ultra-finely ground into 3-10 μm to obtain a third intermediate product.

[0062] In one embodiment, the pre-calcination may be performed under an inert atmosphere, the pre-calcination temperature may be 900-1000° C., and the pre-calcination time may be 1-2 hours.

[0063] The inert gas may be conventional inert gases such as nitrogen and argon, which can achieve the effect of this embodiment.

[0064] S500, the third intermediate product is ball-milled again, dried, granulated, and pressed into a rough blank.

[0065] S600, sintering the rough blank at high temperature to obtain a high-toughness thermally conductive ceramic material.

[0066] In one embodiment, the high temperature sintering temperature may be 1350-1500° C., and the high temperature sintering time may be 1-4 hours.

[0067] Based on the preparation methods of the above-mentioned embodiments, a one-dimensional carbon material is subjected to plasma surface roughening treatment, and then mixed with beryllium oxide in water, stirred, centrifuged, and calcined to prepare a beryllium oxide-coated one-dimensional carbon material; the beryllium oxide-coated one-dimensional carbon material is then mixed with aluminum oxide and zirconium oxide and subjected to plasma surface roughening treatment, and then mixed with a thermal conductive toughening agent, pre-fired, pressed, and sintered at high temperature, to prepare a ceramic material with excellent strength, toughness and thermal conductivity, which can meet the needs of new energy battery cover plates, and at the same time, the raw materials are widely available and the cost is relatively low.

[0068] The effects of the technical solution of the present application are further described in detail below in conjunction with specific embodiments.

[0069] Embodiment 1:

[0070] A high-toughness thermally conductive ceramic material, comprising the following raw materials in parts by weight: 79 parts of aluminum oxide; 13 parts of zirconium oxide; 8 parts of a thermally conductive toughening agent; and 8 parts of a beryllium oxide-coated one-dimensional carbon material.

[0071] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with alumina, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 10 parts of graphitized carbon, 10 parts of Tween, 50 parts of alumina, 10 parts of zirconium oxide, 8 parts of long-chain amino acid modified silica gel particles, and 17 parts of high-density polyethylene.

[0072] The preparation method of the above-mentioned high-toughness thermally conductive ceramic material comprises:

[0073] Plasma surface roughening treatment of one-dimensional carbon materials;

[0074] Beryllium oxide was added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 5 hours; then aged and centrifuged, the precipitate was washed, and dried at 80°C for 10 hours; then transferred to a muffle furnace and heated to 980°C at a rate of 10°C / min for calcination for 4 hours, and ultra-finely ground to 0.5-5μm to obtain a beryllium oxide-coated one-dimensional carbon material;

[0075] Alumina and zirconium oxide are mixed and ball-milled for 4 hours, and then uniformly mixed with beryllium oxide-coated one-dimensional carbon material, and plasma surface roughening treatment is performed; then uniformly mixed with a thermal conductive toughening agent, pre-calcined for 1 hour in a nitrogen atmosphere, and ultra-finely ground to 3-10 μm to obtain a second intermediate product;

[0076] The second intermediate product is ball-milled again, dried, granulated, and pressed at 50 MPa to obtain a rough blank;

[0077] The rough blank is sintered at 1480°C for 2 hours to obtain a high-toughness thermally conductive ceramic material.

[0078] Embodiment 2:

[0079] A high-toughness thermally conductive ceramic material, the preparation method is the same as that of Example 1, except that:

[0080] The high-toughness thermally conductive ceramic material of Example 2 comprises the following raw materials in parts by weight: 85 parts of aluminum oxide; 10 parts of zirconium oxide; 12 parts of thermally conductive toughening agent; 10 parts of beryllium oxide-coated one-dimensional carbon material;

[0081] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with alumina, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 12 parts of graphitized carbon, 12 parts of Tween, 55 parts of alumina, 8 parts of zirconium oxide, 6 parts of long-chain amino acid modified silica gel particles, and 15 parts of high-density polypropylene.

[0082] Embodiment 3:

[0083] A high-toughness thermally conductive ceramic material, the preparation method is the same as that of Example 1, except that:

[0084] The high-toughness thermally conductive ceramic material of Example 3 comprises the following raw materials in parts by weight: 70 parts of aluminum oxide; 15 parts of zirconium oxide; 10 parts of thermally conductive toughening agent; 5 parts of beryllium oxide-coated one-dimensional carbon material;

[0085] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with alumina, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 8 parts of graphitized carbon, 8 parts of Tween, 45 parts of alumina, 12 parts of zirconium oxide, 10 parts of long-chain amino acid modified silica gel particles, and 20 parts of high-density polyolefin elastomer.

[0086] Comparative Example 1:

[0087] A high-toughness thermally conductive ceramic material, which is basically the same as Example 1, except that:

[0088] The high-toughness thermally conductive ceramic material of Comparative Example 1 does not contain beryllium oxide-coated one-dimensional carbon material.

[0089] Comparative Example 2:

[0090] A high-toughness thermally conductive ceramic material, which is basically the same as Example 1, except that:

[0091] The high-toughness thermally conductive ceramic material of Comparative Example 2 uses raw materials in which the particle size of aluminum oxide ranges from 10 to 30 μm.

[0092] Comparative Example 3:

[0093] A high-toughness thermally conductive ceramic material, which is basically the same as Example 1, except that:

[0094] The materials of Comparative Example 3 include the following raw materials in parts by weight: 79 parts of aluminum oxide; 13 parts of zirconium oxide; 3 parts of thermal conductive toughening agent; and 8 parts of beryllium oxide-coated one-dimensional carbon material.

[0095] Comparative Example 4:

[0096] A high-toughness thermally conductive ceramic material, which is basically the same as Example 1, except that:

[0097] The material of Comparative Example 4 uses silica gel particles to replace the long-chain amino acid modified silica gel particles of Example 1, and in the preparation method of Comparative Example 4, the aluminum oxide, zirconium oxide and beryllium oxide coated one-dimensional carbon material are uniformly mixed without being subjected to plasma surface roughening treatment.

[0098] Effect example:

[0099] The materials of Example 1 and Comparative Examples 1 to 4 were used as samples, and the flexural strength and fracture toughness of the samples were measured using an electronic universal testing machine. The room temperature thermal diffusion coefficient of the samples was tested using a laser thermal conductivity meter (Germany), and the thermal conductivity of the samples was calculated to obtain the data in the following table.

[0100]

[0101] As shown in the above table, the material of Example 1 has excellent flexural strength, fracture toughness and thermal conductivity, wherein the flexural strength reaches 250 MPa, the thermal conductivity reaches 70 W / (m·K), and the fracture toughness reaches 8.1 MPa·m 1 / 2 , which can meet the needs of new energy battery covers.

[0102] The material of Comparative Example 1 does not use beryllium oxide-coated one-dimensional carbon material, and lacks a network structure constructed by dispersed beryllium oxide-coated one-dimensional carbon material. Therefore, the fracture toughness and thermal conductivity are significantly lower than those of Example 1.

[0103] The material of Comparative Example 2 uses large-particle zirconium oxide as raw material. The particle size is too large, which is not conducive to improving the thermal conductivity and fracture toughness of the material.

[0104] The amount of thermal conductive toughening agent added in the material of Comparative Example 3 is too low, resulting in the fracture toughness and thermal conductivity of the material being significantly lower than those of other embodiments and comparative examples.

[0105] The material of Comparative Example 4 uses ordinary silica gel particles, which cannot give the material excellent hydrophilic properties. Therefore, the sintering density of the material is lower than that of Comparative Example 1. At the same time, it has not undergone plasma surface roughening treatment, which affects the bonding strength and interface properties of the composite material, resulting in the material's flexural strength, fracture toughness and thermal conductivity being lower than those of Example 1.

[0106] It can be seen from the above experimental results that the thermal conductive toughening agent of the present application can significantly improve the thermal conductivity, toughness and strength of the material. The reason is that graphitized carbon has excellent thermal conductivity. At the same time, the addition of long-chain amino acid modified silica gel particles can improve the hydrophilicity of the material, increase the sintering density, and help improve the mechanical strength and thermal conductivity of the material. The high polymer also further improves the toughness and strength of the material.

[0107] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.

[0108] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-toughness thermally conductive ceramic material, characterized in that: It includes the following raw materials in parts by weight: 70-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 8 to 12 parts of thermal conductive toughening agent; 5 to 10 parts of beryllium oxide coated one-dimensional carbon material; Wherein, the thermal conductive toughening agent includes long-chain amino acid modified silica gel particles and graphitized carbon.

2. The high-toughness thermally conductive ceramic material according to claim 1, characterized in that: The particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material is 0.5 to 5 μm, and the particle sizes of aluminum oxide and zirconium oxide are 0.5 to 5 μm.

3. The high-toughness thermally conductive ceramic material according to claim 1, characterized in that: The thermal conductive toughening agent comprises the following components in parts by weight: 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 6-10 parts of long-chain amino acid modified silica gel particles, and 15-20 parts of high polymer; The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer.

4. The high-toughness thermally conductive ceramic material according to claim 1, characterized in that: The beryllium oxide coated one-dimensional carbon material is beryllium oxide coated carbon fiber or beryllium oxide coated carbon nanotube.

5. The high-toughness thermally conductive ceramic material according to claim 1, characterized in that: The high-toughness thermal conductive ceramic material has a bending strength of ≥250MPa, a thermal conductivity of ≥70W / (m·K), and a fracture toughness of ≥8MPa·m 1 / 2 .

6. A method for preparing the high-toughness thermally conductive ceramic material according to any one of claims 1 to 5, characterized in that: include: Beryllium oxide is added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 4 to 6 hours to obtain a first intermediate product; The first intermediate product is aged and centrifuged, and the precipitate is washed, dried, calcined, and ultrafinely ground to 0.5 to 5 μm to obtain a beryllium oxide-coated one-dimensional carbon material; The aluminum oxide and the zirconium oxide are mixed and ball-milled, and then uniformly mixed with the beryllium oxide-coated one-dimensional carbon material and subjected to plasma surface roughening treatment to obtain a second intermediate product; The second intermediate product and the thermal conductive toughening agent are mixed uniformly and pre-sintered, and ultra-finely ground to 3-10 μm to obtain a third intermediate product; The third intermediate product is ball-milled again, dried, granulated, and pressed to obtain a rough blank; The rough blank is sintered at high temperature to obtain a high-toughness thermally conductive ceramic material.

7. The preparation method according to claim 6, characterized in that: The step of adding beryllium oxide into water, then adding one-dimensional carbon material and Tween-80, and stirring for 4 to 6 hours to obtain the first intermediate product also includes: The one-dimensional carbon material is subjected to plasma surface roughening treatment.

8. The preparation method according to claim 6, characterized in that: In the steps of aging and centrifuging the first intermediate product, washing, drying and calcining the precipitate, the calcination temperature is 950 to 1600° C. and the calcination time is 3 to 5 hours.

9. The preparation method according to claim 6, characterized in that: In the step of uniformly mixing the second intermediate product and the thermally conductive toughening agent and pre-firing, the pre-firing is carried out in an inert atmosphere, the pre-firing temperature is 900 to 1000° C., and the pre-firing time is 1 to 2 hours; In the step of sintering the rough blank at high temperature, the temperature of the high temperature sintering is 1350-1500° C., and the time of the high temperature sintering is 1-4 hours.

10. A new energy battery cover, characterized in that: It is prepared by using the high-toughness thermally conductive ceramic material described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-thermal-conductivity conductive carbon fiber polymer-based composite material and preparation method thereof

    CN111534049A

  • High-thermal-conductivity material and preparation method thereof

    CN115073067A

  • High-thermal-conductivity aluminum oxide ceramic material and ceramic circuit substrate

    CN116239367A

  • Heat-conducting ceramic silica gel and preparation method thereof

    CN117024967A

  • Conductive, multilayer-structured resin particles and anisotropic conductive adhesives using the same

    US6352775B1